A comparative analysis of the human resource management and development practices of Central Bicol State University of Agriculture and University of Baguio (UB) - Cordova, Wilson (Animo Repository, 2012)
The purpose of this study is to establish a comparison between Private and Public Institutions in the Philippines, the Central Bicol State University of Agriculture (CBSUA), a public institution and University of Baguio (UB), a private institution regarding the extent of implementation of Human Resources Management and Development (HRMD) practices. The data for the study will be collected through a questionnaire comprising items mainly related to recruitment and placement, training and development, performance appraisal, compensation and benefits and employee relations. The study is a qualitative case analysis. It aims to see the similarities and or differences between a public and a private institution in the Philippines. Recommendations will be made for the improvement of HRMD practices among these identified institutions. Were very much similar in most of the aspects of the HRM practices that were compared regardless on which sector they belong, whether a public or a private higher education institution. At the end, recommendations were made for the improvement of HRM practices among these institutions.